Performance Analysis of the Unsignalized Nusantara Cilacap Three-Way Intersection Based on the 2023 Indonesian Road Capacity Guidelines - Muhamad Sofi Ardani; Nur Indah Wardani; Annisa Yuliana Angeline; Sari Sekar Ningrum; Zhilal Shadiq (International Journal Labs, 2026)
The increase in traffic volume, especially during long holidays coinciding with Eid al-Adha, can affect intersection performance and potentially cause issues such as changes in intersection capacity, degree of saturation, and traffic delays. Therefore, an analysis of intersection performance is necessary to evaluate the level of service at the Nusantara Three-Way Intersection in Cilacap. This study aims to calculate the intersection capacity, degree of saturation, traffic delay, and determine the level of service of the Nusantara Three-Way Intersection due to increased traffic volume. This research uses a quantitative approach based on primary and secondary data. The analysis was conducted according to the provisions of the Indonesian Road Capacity Guidelines (PKJI) 2023. The results show that the peak traffic volume occurred on Thursday, 5 June 2025, at 16:00– 17:00 WIB with a value of 886.40 PCU/hour (SMP/hour). The intersection capacity was 2,414.886 PCU/hour, with a degree of saturation of 0.367 and an average delay of 4.799 seconds per vehicle. The performance of the Nusantara Three-Way Intersection can be categorized as good, indicating that the level of service is still optimal and no additional lanes or traffic management measures are required